STUDI MOLECULAR DOCKING SENYAWA GOLONGAN FLAVONOL SEBAGAI ANTIBAKTERI - Isna Wardaniati; Muhammad Azhari Herli (JURNAL FARMASI DAN MAKANAN, 2018)
In this paper we studied the bioactive compounds of Flavonol-D-alanil D-alanin dekarboksipeptidase receptor interactions In silico. First, prepared three dimensional structure of D-alanil D-alanin dekarboksipeptidase as receptor. Preparation of fourth bioactive compounds of flavonol which will be as ligands, klokasilin and D-alanil D-alanin as a comparison. The fourth bioactive compounds of flavonol, klokasilin and D-alanil D-alanin were docked with D-alanil D-alanin dekarboksipeptidase until energy values were obtained. The fourth bioactive compounds of flavonol had lesser binding energy values than D-alanil D-alanin, Quercitrine and rutin also predicted to have greater binding energy and binding affinity than klokasilin (antibiotic) and D-alanil D-alanin (nature ligand).